1997
DOI: 10.1136/ard.56.9.516
|View full text |Cite
|
Sign up to set email alerts
|

Long term prognosis of reactive salmonella arthritis

Abstract: Objectives-Reactive joint complications triggered by salmonella gastroenteritis are increasingly reported, but the outcome and long term prognosis of the patients is incompletely known. This study looked at the prognosis of salmonella arthritis in patients hospitalised in 1970-1986. Methods-Hospital records from two hospitals in southern Finland were screened for patients with the discharge diagnosis of salmonellosis or reactive, postinfectious arthritis or Reiter's disease. For the patients with confirmed dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 21 publications
0
43
0
1
Order By: Relevance
“…While ReA in many cases follows a self-limited course, we found that of 27 patients with acute post-Salmonella ReA, 18 still had persisting disease activity at a 5-year follow-up (20). PostSalmonella ReA can be accompanied by erosive sacroiliitis (13). Despite the strong temporal association with antecedent infection, the pathogenesis of ReA is not resolved, but there is strong evidence of local persistence of microbial antigens (6) and microbial nucleic acids (4).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…While ReA in many cases follows a self-limited course, we found that of 27 patients with acute post-Salmonella ReA, 18 still had persisting disease activity at a 5-year follow-up (20). PostSalmonella ReA can be accompanied by erosive sacroiliitis (13). Despite the strong temporal association with antecedent infection, the pathogenesis of ReA is not resolved, but there is strong evidence of local persistence of microbial antigens (6) and microbial nucleic acids (4).…”
mentioning
confidence: 81%
“…There is evidence clinically, in the case of post-Salmonella ReA (13), and experimentally, in the case of synovial fibroblast-packaged pathogens (9), that antecedent infection can set in motion a pathological sequence of events resulting in erosive arthritis, particularly of the sacroiliac joint. However, the re- lationship between the microbial trigger and the resulting sacroiliitis is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Leirisalo-Repo et al reported that only 20% of their cases of inpatient Salmonella arthritis were completely normal at a mean of 11 years (119). A prolonged (Ͼ1-year) extension of acute arthritis has been described in about 4% of cases of Yersinia arthritis, in 19% of cases of Salmonella arthritis, in 19% of cases of Shigella arthritis, and in 17% of cases Chlamydia arthritis (91,119,120). Depending on the triggering infection and on the follow-up time, chronic arthritis is observed in 2 to 18% of patients, sacroiliitis is observed in 14 to 49%, and AS is observed in 12 to 26% (91,117,200).…”
Section: Coursementioning
confidence: 99%
“…When all symptoms are taken into account, 75% of patients are in complete remission at the end of the second year after onset. In the Finnish study, 15% of patients developed chronic sequelae or proceeded into chronic SpA (89,120). Leirisalo-Repo et al reported that only 20% of their cases of inpatient Salmonella arthritis were completely normal at a mean of 11 years (119).…”
Section: Coursementioning
confidence: 99%
“…If arthritis, conjunctivitis and urethritis are present as a triad, reactive arthritis might be referred to as Reiter's syndrome. c. A number of children, particularly those with HLA-B27, develop a chronic course, and may even develop AS (Leirisalo, Skylv et al 1982;Hussein 1987;Artamonov, Akhmadi et al 1991;Cuttica, Scheines et al 1992;Yli-Kerttula, Tertti et al 1995;Leirisalo-Repo, Helenius et al 1997;Leirisalo-Repo 1998). Children without HLA-B27 who have ReA, particularly when the disease is triggered by Yersinia or Campylobacter, usually have a rather short and benign course.…”
Section: Reactive Arthritis (Rea)mentioning
confidence: 99%